Is love the answer? - Isaki, Uta (Kodansha USA Publishing, LLC, 2023)
"A poignant coming-of-age story about a young woman coming into her own as she discovers her identity as aromantic asexual. When it comes to love, high schooler Chika wonders if she might be an alien. She's never fallen for or even had a crush on anyone, and she has no desire for physical intimacy. Her friends tell her that she just 'hasn't met the one yet,' but Chika has doubts...It's only when Chika enters college and meets peers like herself that she learns there's a word for what she feels inside--asexual--and she's not the only one. After years of wondering if love was the answer, Chika realizes that the answer she long sought may not exist at all--and that that's perfectly normal" -- Page [4] of cover.